2021
DOI: 10.1007/s40123-021-00375-w
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Factors Associated with the Amount of Visual Field Damage in Eyes with Newly Diagnosed, Untreated, Open-angle Glaucoma

Abstract: Introduction:The aim of this study was to evaluate the correlation between several ocular parameters (intraocular pressure [IOP], corneal biomechanical properties) and the visual field (VF) mean deviation (VF MD) in eyes with openangle glaucoma (OAG). Methods: We conducted a cross-sectional, observational study in which we measured the IOP with Goldmann applanation tonometry, the central corneal thickness (CCT), and the corneal parameters obtained from the Ocular Response AnalyzerÒ (ORAÒ) and the CorvisÒ ST no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
(24 reference statements)
1
6
0
Order By: Relevance
“…IOP lowering medications, particularly the prostaglandin analogues, have been shown to influence corneal biomechanics significantly. 17 – 19 Our results were in agreement with the study from Bolivar et al, 40 which found that the initial Corvis ST biomechanical parameters (DA, AT1, AV1, AT2, AV2, HC time, HC PD, HC radius) had no significant correlation with MD in treatment naïve POAG eyes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…IOP lowering medications, particularly the prostaglandin analogues, have been shown to influence corneal biomechanics significantly. 17 – 19 Our results were in agreement with the study from Bolivar et al, 40 which found that the initial Corvis ST biomechanical parameters (DA, AT1, AV1, AT2, AV2, HC time, HC PD, HC radius) had no significant correlation with MD in treatment naïve POAG eyes.…”
Section: Discussionsupporting
confidence: 90%
“…Several previous studies reported the lack of association between IOP and MD in untreated POAG patients as well. 40 , 45 Also, there was a study that observed that age was not correlated with glaucoma severity in POAG patients. 15 The lack of association between IOP and age with glaucoma severity in our study may be explained by the cross-sectional design and small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…However, no significant difference was observed in CH between the control and treatment-naïve POAG groups, with the AUC value as low as 0.59. Few studies have investigated CH in treatment-naïve glaucomatous eyes, some of which were lower than that in the current treatment-naïve POAG eyes (9.71 mmHg) 52,53 . A prospective study by Susanna et al indicated that CH is a risk factor for the development of glaucoma even when a multivariable model to adjust for the treatment was used 10 .…”
Section: Discussionmentioning
confidence: 60%
“…A prospective study by Susanna et al indicated that CH is a risk factor for the development of glaucoma even when a multivariable model to adjust for the treatment was used 10 . Boliver et al 52 found that CH (8.9 mmHg in average) was associated with the amount of VF damage in treatment-naïve OAG eyes. Prata et al 53 found an association between CH (8.1 mmHg in average) and optic nerve head morphology in untreated newly diagnosed patients with POAG.…”
Section: Discussionmentioning
confidence: 99%
“…10 Boliver et al found that CH was associated with the amount of VF damage in treatment-naïve OAG eyes. 49 Prata et al found an association between CH and optic nerve head morphology in untreated newly diagnosed patients with POAG. 50 The entire reason for the contradictory results is unknown; however, it could be attributed to the difference in IOP levels.…”
Section: Discussionmentioning
confidence: 99%